Expression of Anaplastic Lymphoma Kinase (ALK) in glioma and possible clinical correlations. A retrospective institutional study - Mohammed A. Azab (Cancer Treatment and Research Communications, 2023)
Background: Glioblastoma is considered the most aggressive primary brain tumor. Recurrence after treatment is a significant problem with a failed response to optimal treatment. The recurrence of GBM is linked to different cellular and molecular pathways. Nationwide, in Egypt, astrocytic tumors are the most commonly diagnosed CNS tumor. Anaplastic Lymphoma Kinase (ALK CD246) is an enzymatic protein (RTK) belonging to the insulin receptors superfamily. Methods: This is a retrospective study including sixty cases of astrocytic tumors (males = 40, mean age = 31.5), (females = 20, mean age = 37.77) obtained through collecting archived paraffin blocks of astrocytic tumor from the Pathology Department, Cairo University Faculty of Medicine during the period from January 2015 till January 2019. All cases were evaluated for ALK expression trying to find any clinical correlations with the clinical data. Results: Correlations were made using a scatterplot matrix correlogram. There was a significant correlation between tumor recurrence and ALK expression (r = 0.8, P < 0.01), and incidence of postoperative seizures (r = 0.8, P < 0.05), and between mean age and score tumor (r = 0.8, P < 0.05). Conclusion: Expression of ALK was found to be abundant among high-grade gliomas and tumor recurrence rate was higher in ALK-positive patients. Further studies are needed to evaluate the potential use of ALK as a prognostic marker in cases of GBM.